Optimization of the Security Unit's Performance in the Intelligence Division for Early Detection of Motor Vehicle Theft Crimes in the Demak Police Jurisdiction. - M.Ikbal Jolanda (Tanggon Kosala, 2022)
The focus of research in this final project is the optimization of the performance of the Satintelkam security unit in the early detection of curanmor crimes in jurisdiction Demak police region. This research focus is considered important because the theft of motorized vehicles over the past three years in Demak Regency has increased. Therefore, Satintelkam Demak police region seeks to optimize the performance of the Satintelkam security unit in early intelligence detection so that its implementation is in accordance with Perkabik No.1 of 2013 concerning Police Intelligence Investigation. This research aims to: (1) describe the performance of the Satintelkam Security Unit in the early detection of curanmor crimes, (2) find and describe efforts to optimize the performance of the Satintelkam Security Unit in the early detection of curanmor crimes in the Demak Police jurisdiction. In the conceptual literature to analyze the above problems, several theories are used in this study, namely; Management theory, and SWOT Analysis theory. While the concepts used as a theoretical basis, namely; the concept of optimization, the concept of Intelligence, the concept of performance, the concept of motor vehicle theft, and the concept of Early Detection. In this research, a qualitative method with descriptive analysis is used to process data and field research to obtain data directly by participantobservation. Primary and secondary data sources, using data triangulation to obtain data validity. The results of the findings during this study are (1) The performance of the Satintelkam Security Unit is still not optimal, the implementation of early detection has not been fully adapted to Perkabik No.1 of 2013 concerning Intelligence Investigation, such as the absence of checks in making daily mutation books, the unavailability of special investigation tools, the delivery of intelligence information is not in accordance with procedures. (2) Efforts to optimize the performance of the Satintelkam security unit in early detection are hampered due to limited training quotas and dikjur / dikbangspes to improve the competence of personnel, adjusting the qualifications of members in the field that are not implemented due to the limited number of personnel. Conclusions in this final project, (1) The performance of the Satintelkam Security Unit in early detection is still lacking, the implementation of early detection must comply with Perkabik No.1 of 2013. (2) Efforts to optimize Satintelkam's performance in early detection have not been carried out properly due to lack of coordination with Satreskrim and the implementation of early detection which is only backup from Satreskrim.